(untitled) (Revista de História Regional, 2007)
The geography of knowledge deals with the relation between transformations of the physical environment and its ideological interpretations, differentiating space according to philosophical and religious attitudes. Brazil is used as an example to demonstrate how the dispute between modernist ideology, mainly represented by the Brazilian political and intellectual elite, and religious interpretations, which are the predominant forms of cultural expression among large portions of the Brazilian population, are intermingled in the geography of knowledge of this country. It could be shown, that modernism found its way through scholastic elements of the official Catholic Church, the Jesuitical enterprise, the absolutist transformations introduced by the Marquês de Pombal, the romantic idea of Nationality of the Empire, and the propulsion of technological advance and education throughout the Old Republic, the Estado Novo and the newer Republics. On the other hand, a large and very differentiated field of religious interpretations of space, like the hierarchical space of the Catholic church, the syncretistic space of caboclo culture, the life-world approach of protestant churches, the rhizomatic space of Afro-Brazilian religions and the fluid space of Amerindians religions enter into a dialogical and often conflictive relationship with official, modern ideology and its spatial expressions.